Some mechanisms of the protective effect of ischemic preconditioning on rat liver ischemia-reperfusion injury - Adam ANI (International Journal of General Medicine, 2014)
Abdel Nasser Ismail Adam Physiology Department, Medical Research Institute, Alexandria University, Alexandria, Egypt Abstract: Ischemia-reperfusion (I/R) injury is a multifactorial process that affects graft function after liver transplantation. An understanding of the mechanisms involved in I/R injury is essential for the design of therapeutic strategies to improve the outcome of liver transplantation. The generation of reactive oxygen species subsequent to reoxygenation inflicts tissue damage and initiates a cascade of deleterious cellular responses, leading to inflammation, cell death, and ultimate organ failure. Increasing experimental evidence has suggested that Kupffer cells and T-cells mediate activation of neutrophil inflammatory responses. Activated neutrophils infiltrate the injured liver in parallel with increased expression of adhesion molecules on endothelial cells. The heme oxygenase system is among the most critical of the cytoprotective mechanisms activated during cellular stress, exerting antioxidant and anti-inflammatory functions, modulating the cell cycle, and maintaining the microcirculation. Finally, the activation of toll-like receptors on Kupffer cells may play a fundamental role in exploring new therapeutic strategies based on the concept that hepatic I/R injury represents a case for host “innate” immunity. In the present study, there was a significant decrease in hepatic activity of glycogen in the I/R group as compared with corresponding values in the control group. On the other hand, there was a significant increase in the hepatic activity of glycogen in the I/R-IP (ischemic preconditioning) group as compared with corresponding values in the I/R group. Keywords: liver, ischemic preconditioning, reperfusion injury, oxidative stress, nitric oxide, caspase, glycogen